Catheter-directed thrombolysis for deep vein thrombosis: 2021 update. (December 2021) - Goldhaber, Samuel Z; Magnuson, Elizabeth A; Chinnakondepalli, Khaja M; Cohen, David J; Vedantham, Suresh
Catheter-directed thrombolysis (CDT) has been utilized as an adjunct to anticoagulant therapy in selected patients with deep vein thrombosis (DVT) for approximately 30 years. CDT used to be limited to patients with DVT causing acute limb threat and those exhibiting failure of initial anticoagulation, but has expanded over time. Randomized trials evaluating the first-line use of CDT for proximal DVT have demonstrated that CDT does not produce a major reduction in the occurrence of post-thrombotic syndrome (PTS) and that it is poorly suited for elderly patients and those with limited thrombus extent or major risk factors for bleeding. However, CDT does offer selected patients with acute iliofemoral DVT improvement in reducing early DVT symptoms, in achieving reduction in PTS severity, and in producing an improvement in health-related quality of life (QOL). Clinical practice guidelines from medical and surgical societies are now largely aligned with the randomized trial results. This review offers the reader an update on the results of recently completed clinical trials, and additional guidance on appropriate selection of patients with DVT for catheter-directed thrombolytic therapy.